Kondisi Haid sebagai Penyebab Qada Salat Perspektif Imam Syafii dan Syekh al-‘Uṡaimīn: The Condition of Menstruation as a Cause for Qada Prayer: The Perspectives of Imam Shafi'i and al-‘Uṡaimīn - Nuraeni Novira; Muttazimah, Muttazimah; Mei Rahayu (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
In Islam, menstruating women are not obligated to perform prayers (ṣalāh) and are not required to make them up. However, if menstrual blood appears unknowingly when the prayer time has arrived, scholars have differing opinions regarding the obligation of performing the prayer in such a condition. This study aims to examine the views of Imam Shafi'i and Sheikh al-‘Uthaymeen regarding menstruation conditions that necessitate a woman to make up her missed prayers, as well as to identify the similarities and differences in their opinions. The research employs a qualitative descriptive approach (non-statistical), focusing on textual and scriptural studies, using normative, historical, and comparative methods. The findings of this research indicate that a menstruating woman is required to make up her missed prayer if she attains purity at the end of the prayer time and has enough time to perform at least one rak‘ah before the time expires. In this case, she must perform the prayer after taking a ritual bath (ghusl). Additionally, if menstruation begins after the prayer time has entered, but she has not yet prayed, she must make it up after attaining purity. This opinion is held by both Imam Shafi'i and Sheikh al-‘Uthaymeen.Another condition discussed is when a woman attains purity during the time of ‘Asr prayer; according to Imam Shafi'i, she is required to combine it with the Dhuhr prayer. Likewise, if she becomes pure during the time of ‘Isha prayer, she must also perform the Maghrib prayer. However, Sheikh al-‘Uthaymeen disagrees with this view and holds that she is only required to perform ‘Asr or ‘Isha without having to combine it with the preceding prayer.Furthermore, if a woman has attained purity but intentionally delays taking the ritual bath until the prayer time expires, Imam Shafi'i mandates her to make up the missed prayer, whereas Sheikh al-‘Uthaymeen does not obligate her to do so. Instead, he advises her to repent frequently and engage in righteous deeds.